Uptake of community-based differentiated antiretroviral therapy service delivery and associated factors among people living with HIV in Ethiopia: a multicenter cross-sectional study - Merid, Fasika; Toma, Temesgen Mohammed; Anbesie, Abraham; Guyo, Tamirat Gezahegn (Frontiers in Public Health, 2024)
Background Achieving the 95–95–95 targets require an efficient and innovative person-centered approach, specifically community-based differentiated service delivery (DSD), to improve access to human immunodeficiency virus (HIV) services and reduce burdens on the health system. Therefore, this study aimed to assess the uptake of community-based DSD models and associated factors among people living with HIV (PLHIV). Methods A multicenter cross-sectional study was conducted among PLHIV in public health facilities in South Ethiopia. Data were collected and entered into EpiData version 3.1 before being exported to Stata version 14 for further analysis. In the bivariable logistic regression analysis, variables with a p-value of ≤0.25 were included in the multivariable logistic regression analysis. A p-value of <0.05 was used to identify statistically significant factors. Results Among 381 stable PLHIV, 55.91% were women. The median age (interquartile range) was 40 years (27–53). The uptake of community-based DSD models was 19.16%. Residence and disclosure were the two independent factors significantly associated with the uptake of community-based DSD models. Conclusion One out of five stable PLHIV on antiretroviral therapy uptake the community-based DSD models. Improvement in uptake is needed in Ethiopia's resource-limited healthcare system to better achieve the 95-95-95 targets.